Social media and society : an introduction to the mass media landscape - Luttrell, Regina, 1975-; Wallace, Adrienne A., 1976- (Rowman & Littlefield, 2021)
"This text engages students in the social media phenomenon, exploring how fundamental changes in mass media influence every level of societal communication. With the explosion of social media and big data, students must become conscious of media's positive and negative influences on their lives"- Resumé vydavatele